Profile of Fournier gangrene patients using hyperbaric oxygen therapy as an adjuvant treatment - Tikami, Katia Fumika; Simão, José Cláudio [UNESP]; Passerotti, Larissa Camargo; Almeida Barbosa, Adriana Sierra Assencio (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2020)
Objective: Evaluating the results obtained from hyperbaric oxygen therapy (HBOT) as an adjuvant treatment in Fournier's Gangrene (GF). Casuistic and Method: Cross-sectional, retrospective, and descriptive study based on the analysis of physical records of patients with GF submitted to hyperbaric oxygen therapy through the hyperbaric chamber from February 2008 to May 2018, assisted at the hyperbaric oxygen therapy clinic, in Bauru, SP. The data collected were age, gender, etiology, comorbidities, lesion location and extension, total session number, and mortality. Result: It totaled 38 patients, 76% male, with a mean age of 55.6 years. Among the patients, 17 (44.7%) were discharged, 18 (47.4%) discontinued treatment before termination, and three (8.21%) deaths occurred. The main etiology was an abscess and the main predisposing comorbidities were diabetes mellitus and hypertension. The location and extension lesion with the most affected areas were in the scrotal region, followed by the perineal region. Conclusion: The results of this study demonstrated that the effect of HBOT as an adjuvant treatment has an advantage in the treatment of GF resulting in considerable patient medical discharge and low mortality.
Perfil dos pacientes com gangrena de Fournier utilizando a oxigenoterapia hiperbárica como tratamento adjuvante
Keywords: Combined Modality Therapy; Fournier Gangrene; Hyperbaric Oxygenation